South-Western Federal Taxation 2021: Corporations, Partnerships, Estates and Trusts, 44th Edition - William Raabe (Cengage Learning, 2020)
Guide students through today's corporate tax concepts as they gain an understanding of ever-changing tax laws with Raabe/Young/Nellen/Hoffman/Maloney's SOUTH-WESTERN FEDERAL TAXATION 2021: CORPORATIONS, PARTNERSHIPS, ESTATES & TRUSTS, 44E. This leading solution helps students grasp the impact of tax concepts on corporations and partnerships as well as estates and trusts. Updated coverage details the most current tax law at the time of publication, including recent tax changes. Complete coverage of the Tax Cuts and Jobs Act of 2017 offers related guidance from the Treasury Department. Numerous clear examples, memorable summaries and tax scenarios sharpen critical-thinking, writing and research skills, while sample C.P.A. exam questions help students prepare for the current exam.